2018
DOI: 10.1016/j.jnucmat.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the spatial variability of material properties of Gilsocarbon and NBG-18 using random fields

Abstract: ☆ This manuscript has been authored by UT-Battelle, LLC, under contract DE-AC05-00OR22725 with the US Department of Energy (DOE). The US government retains and the publisher, by accepting the article for publication, acknowledges that the US government retains a nonexclusive, paid-up, irrevocable, worldwide license to publish or reproduce the published form of this manuscript, or allow others to do so, for US government purposes. DOE will provide public access to these results of federally sponsored research i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 29 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…These sources of variability in the graphite materials make each grade unique. Microstructural and property variations are also expected across large components of graphite [2 , 3] . Overall descriptions of the phases of graphite and micrographs in Fig.…”
Section: Data Descriptionmentioning
confidence: 96%
“…These sources of variability in the graphite materials make each grade unique. Microstructural and property variations are also expected across large components of graphite [2 , 3] . Overall descriptions of the phases of graphite and micrographs in Fig.…”
Section: Data Descriptionmentioning
confidence: 96%
“…The size and nature of filler particles can introduce significant variations to the mechanical properties of graphite. Previous research has shown that a graphite component can have different properties at different locations within the component [2 , 3] . Grain size or filler particle size can also influence graphite's fracture roughness with coarser grades yielding greater fracture roughness [4] .…”
Section: Data Descriptionmentioning
confidence: 99%
“…Manufacturing methods and raw materials can affect graphite's heterogeneity and microstructural characteristics. Even with similar production conditions and raw materials, material variability can be present within a billet, between billets, and between different batches of graphite [50,51]. This part of the project will assess batch-to-batch intervariability using PCEA graphite.…”
Section: Intragrade Variations Of Microstructural Characteristics And...mentioning
confidence: 99%